Exploratory analysis of epilepsy biomarkers using untargeted metabolomics across multiple cohorts - Oja, Kaisa T.; Ilisson, Mihkel; Reinson, Karit; Muru, Kai; Reimand, Tiia; Peterson, Hedi; Fishman, Dmytro; Haller, Toomas; Kronberg, Jaanika; Estonian Biobank Research Team,; Wojcik, Monica H.; Kennedy, Adam D.; et al. (Frontiers in Neurology, 2025)
IntroductionEpilepsy is a common central nervous system disorder characterized by abnormal brain electrical activity. Diagnosing epilepsy can be challenging, as it has various causes and different clinical manifestations. We aimed to analyze whether there are similarities in the metabolic profiles of patients with epilepsy despite different etiology, seizure frequency, seizure type, and patient age.MethodsUntargeted metabolomics analysis results were analyzed in three cohorts. The pediatric cohort (PED-C) consisted of 110 pediatric individuals with suspicion of a genetic disorder with unclear etiology; the adult cohort (AD-C) of 250 adults from the Estonian Biobank (EstBB), and the elderly cohort (ELD-C) of 583 adults ≥ 69 years from the EstBB. Epilepsy was diagnosed in 35, 11 and 26 cases, respectively.ResultsSignificant differences (FDR corrected p-value <0.05) were detected in the PED-C in eight metabolites, mainly for lipids. Restricting the analysis to individuals with epilepsy and without any changes in brain magnetic resonance imaging increased the number of significant metabolites to 16. Nine significantly altered lipids were found in the AD-C, mainly triacylglycerides (TAGs). In the ELD-C, significant changes in 20 metabolites, including multiple TAGs, were observed in the metabolic profile of participants with previously diagnosed epilepsy.DiscussionSeveral components of cell membranes were among the altered metabolites, indicating that cell membrane fluidity may have a significant role in the mechanism of epilepsy, and changes in lipid balance may indicate epilepsy. However, further studies are needed to evaluate whether untargeted metabolomics analysis could prove helpful in diagnosing epilepsy earlier.